Women’s Studies: Are We "Broad" Enough - Bromley, Victoria; Ahmad, Aalya (Atlantis, 2013)
The authors consider the “naming debate” in Women’s Studies and the implications of the current tendency to broaden the scope of Women’s Studies by including terms such as “gender” or “feminist” in the name. To this debate, they contribute an analysis of how neoliberal ideology attempts to contain Women’s Studies within the policies and discourses of the corporatization of universities. This paper calls for renewed connections between feminist academics and social justice and women’s movements in order to sustain the transformative politics that have always been part of the feminist project.